Black sand as source of catalysts that selectively isomerize α‑ and β‑pinene epoxides (2025)
Black sand (TBS), that is a mining waste, was treated by several procedures for obtaining materials that were tested as catalysts for isomerization of α- and β-pinene epoxides. The materials were obtained by milling (IC), heat treatment (CTT_800) and hydrothermal reaction with H2SO4 (CAT_400). Characterization analysis included NH3-TPD, XRD, Raman, FTIR-pyridine, XPS, and SEM–EDX. The presence of hematite, ilmenite and rutile was identifed by XRD and Raman analysis. FTIR-Py analysis showed only the presence of Lewis sites for CTT_800 and CAT_400, sites that favor aldehyde formation from monoterpene epoxide isomerization. The measured acid content was 364, 316, 214, and 167 µmolNH3/g for CAT_400, CTT_800, IC, and TBS, respectively; the increase of acidity was related with a higher content of hematite and rutile phases after treatment of the mining waste. Fe, Ti, and O were identifed as the main elements of the solids; no S was detected neither by FTIR, nor by XPS analysis. Over CAT_400 catalyst, α-pinene conversion and campholenic aldehyde selectivity were 96% and 64%, respectively. In the case of β-pinene epoxide isomerization, substrate conversion was 98% and myrtanal selectivity was 92%. For reusing tests, several catalyst treatments were evaluated. After fve reuses of CAT_400 for α- and β-pinene epoxide isomerization, selectivity did not change but conversion decreased, which was related to the decrease of strong acid sites and hematite and/or rutile content variation; a good procedure for catalyst activation is the treatment at 300 °C.